Pengaruh Dukungan Organisasi, Hubungan Kerja dan Lingkungan Kerja terhadap Kepuasan Kerja yang berdampak pada Kinerja Karyawan - Ayu Indah Fitriana; Muslim (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to examine the effect of organizational support, work relations and work environment on job satisfaction and the impact of job satisfaction on employee performance. Data was collected from 110 respondents, namely employees of the Directorate General of Intellectual Property using a purposive sampling method, with the criteria of employees/employees who worked at home during the Covid-19 pandemic but are now back at work and have worked for at least 1 year. In the current quantitative research, researchers used primary data and used the Partial Least Square-Structural Equation Modeling (PLS-SEM) research method, with data processing and analysis using SmartPLS 4 software. The results of this study are organizational support has a positive effect on job satisfaction, work relationships have a positive effect on job satisfaction, the work environment has a positive effect on job satisfaction, and job satisfaction has a positive effect on employee performance.